Fecal Microbiota Transplantation Controls Progression of Experimental Autoimmune Hepatitis in Mice by Modulating the TFR/TFH Immune Imbalance and Intestinal Microbiota Composition - Liang, Ma; Liwen, Zhang; Jianguo, Song; Juan, Dai; Fei, Ding; Yin, Zhang; Changping, Wu; Jianping, Chen (Frontiers in Immunology, 2021)
Alterations of the gut microbiota composition, namely dysbiosis, are possible causes for the development autoimmune hepatitis (AIH). This study aimed to investigate the potential effect of fecal microbiota transplantation (FMT) in a murine model of experimental AIH (EAH), a condition more similar to that of AIH patients. Changes in the enteric microbiome were determined by 16S rRNA quantitative PCR in AIH patients. Moreover, secondary aboiotic EAH mice harboring dysbiosis (ABx) were generated by broad-spectrum antibiotic treatment and given FMT through the anus to evaluate the effect of FMT on TFR and TFH cell imbalances and microbial ecologies. Derangement of the intestinal microbiome and bacterial translocation occurred in AIH patients compared to nonalcoholic fatty liver disease patients and HCs. Therapeutic FMT was capable to attenuate liver injury and bacterial translocation in ABx EAH mice. Additionally, FMT significantly increased frequency of splenic TFR cells and reduced frequency of splenic TFH cells in ABx EAH mice. Furthermore, the levels of serum liver enzymes (ALT and AST) of FMT-treated CXCR5-/-EAH mice were partially restored on the 28th days compared to FMT-treated EAH mice. Finally, FMT could effectively restore normobiotic microbial ecologies in EAH mice. Taken together, our findings demonstrated that FMT was capable of controlling hepatitis progression in EAH mice, and the associated mechanism might be involved in the regulation of the TFR/TFH immune imbalance and the restoration of gut microbiota composition.